Bile acids: a potential role in the pathogenesis of pharyngeal malignancy. (18th January 2017) - Shellman, Z.; Aldhahrani, A.; Verdon, B.; Mather, M.; Paleri, V.; Wilson, J.; Pearson, J.; Ward, C.; Powell, J.
Abstract : Objective: Gastro‐oesophageal reflux disease is thought to be a risk factor for head and neck malignancies. Bile acids are one of the principle components of gastric refluxate and have previously been implicated in the development of oesophageal and bowel malignancies. There is clear evidence that bile acids reflux into the laryngopharynx. Despite this, the carcinogenic properties of bile acids in this area are yet to be fully identified. We therefore investigated the potential role of bile acids in pharyngeal malignancy, through the highly conserved process of epithelial–mesenchymal transition (EMT). EMT occurs in invasion and metastasis and is a central process in the development of epithelial carcinoma. Design: Translational research study. Methods: Human hypopharyngeal squamous carcinoma FaDu cells were challenged with primary (cholic or chenodeoxycholic) and secondary (deoxycholic or lithocholic) bile acids. EMT‐relevant proteins TGF‐ β 1 and MMP‐9 were measured in the cell culture supernates at 48 h via ELISA. Cell viability was confirmed >95% via CellTiter‐Blue assay. Results: Significantly greater concentrations of TGF‐ β 1 were measured in the culture supernates of cells treated with cholic acid, deoxycholic acid and chenodeoxycholic acid. MMP‐9 levels were increased in deoxycholic acid and lithocolic acid stimulations when compared to control ( P < 0.05). Conclusion: This is the first demonstration that bile acids induce TGF‐ β 1 and MMP‐9 in pharyngeal cells. TGF‐ β 1 is considered a master switch for EMT, while MMP‐9 is a part of the EMT proteome which degrades basement membranes. This implies a potential role for bile acids in pharyngeal carcinogenesis through the mechanism of EMT and suggests potential novel therapeutic targets.